Diagnosis of extra-adrenal phaeochromocytoma after nephrectomy - Barski, Dimitri (Polish Urological Association, 2014)
This case describes a 50–yr–old man who was admitted to the Urology Ward upon the suspicion of a left kidney tumor. As part of the pre–operative check–up, an ultrasound and computed tomography of the kidneys were conducted. The results confirmed the initial diagnosis. The postoperative diagnosis was extra-adrenal pararenal phaeochromocytoma (ePCC) with succinate dehydrogenase complex, subunit B (SDHB) gene mutation. During the follow–up, a second tumor was detected by 3,4–dihydroxy–6–F–18–fluoro–L–phenylalanine positron emission tomography/computed tomography F–DOPA–PET CT that resulted in another surgery with complete resection of the tumor. The patient and his family were counseled by a genetic laboratory and remain under surveillance.